Exploring the relationship between creativity and cyberloafing of prospective teachers - Akar, Ibrahim; Karabulut Coskun, Burcu (Elsevier BV, 2020)
Abstract The purpose of this research study was to investigate the relationship between creativity and cyberloafing. To achieve this purpose, researchers used the explanatory purposed correlational research design of the quantitative method. Participants were 597 prospective teachers at a college of education at a public university in Turkey. A demographic information form, Kaufman Domains of Creativity Scale (K-DOCS), and Cyberloafing Scale were used to collect data. Preliminary analyses were conducted and Pearson-product moment correlation coefficients were calculated to analyze the data. Findings showed that there is a significant positive but small relationship between creativity and cyberloafing. Furthermore, significant positive but also small relationships were found between creativity scores and cyberloafing subscores, cyberloafing scores and creativity subscores, creativity subscores, and cyberloafing subscores. Only one significant positive but medium relationship was found between creativity subscale 2 (mechanical/scientific) and cyberloafing subscale 5 (gaming/gambling). Findings were discussed concerning the relevant literature and implications for further studies and for the field of teacher education were presented.
Keywords: 4. Education